Human Resource Policies and Work Culture: A Case of Starbucks - Shinta Dewi Sugiharti Tikson (JBMI (Jurnal Bisnis, Manajemen, dan Informatika), 2018)
This paper discusses the human resource management policies and work culture at Starbucks. Starbucks view their employees as company assets that must be managed correctly in order to maintain the most valuable human resources in the business. This company also understand the relationship between positive human resource management policies and work culture and employee motivation. Therefore, the company take great care in selecting the right kind of people and make an effort to retain them. For that reason, the company’s human resource policies reflected its commitment on its employees.Keywords: Human resource policies and practice, work culture, Starbucks, employee motivation.